Degradation of C.I. Reactive Orange 4 and its simulated dyebath wastewater by heterogeneous photocatalysis - Gonçalves, M. Sameiro T. (2005)
The commercial azo dye C.I. Reactive Orange 4 in its reactive and hydrolysed forms can be efficiently photodegraded, using commercial samples of TiO2 as a photocatalyst. With UV light, aqueous solutions containing only dye and no dyebath additives are decolorised slightly more rapidly with Riedel-de-Häen TiO2 than with Degussa P-25 TiO2 . The rate of decolorisation increases markedly with increasing pH. Sunlight is also very effective as a light source. On the other hand, comparison experiments involving UV irradiation of hydrolysed and unhydrolysed Reactive Orange 4 in a simulated spent dyebath showed Degussa P-25 TiO2 to be significantly the more efficient catalyst, giving more than 90% decolorisation after 20 minutes.